Novel Higgs decay signals in R-parity violating models (2008)
ABSTRACT: In supersymmetric models the lightest Higgs boson may decay with a sizable branching ratio into a pair of light neutralinos. We analyze such decays within the context of the minimal supersymmetric standard model with R-parity violation, where the neutralino itself is unstable and decays into standard model fermions. We show that the R-parity violating couplings induce novel Higgs decay signals that might facilitate the discovery of the Higgs boson at colliders (...).